Using spectral reflectance in soybean breeding: evaluating genotypes for soybean sudden death disease resistance and grain yield. - Menke, Ethan J. (Kansas State University, 2018)
Sudden Death Syndrome (SDS) in soybean, (Glycine max ( L.) Merr.) caused by Fusarium virguliforme, is an increasing problem in commercial soybean production due to the yield loss associated with the disease. Screening for genetic resistance requires extensive visual evaluations. Canopy spectral reflectance may be an indirect tool for selection of SDS resistance as well as grain yield in large segregating populations. The objective of this study was to estimate SDS resistance and seed yield in large diverse soybean populations using canopy spectral reflectance. Spectral reflectance, disease index, maturity and yield were measured on two populations consisting of 160 nested association mapping recombinant inbred lines and checks; and 140 commercial cultivars with checks. Populations were grown in three environments in 2015 and 2016 with historic SDS disease pressure. Entry, environment, and entry by environment sources of variation were significant for disease index, yield, maturity and spectral reflectance. Changes in season average reflectance were correlated to disease index, yield and maturity. Estimation models of disease index, yield and maturity were created with season averages as well as individual day readings for both populations. Season average and individual day models accounted for 11% to 77% of the phenotypic variation in disease and 41% to 93% of yield variation when measurements were taken at the height of disease pressure. Models for disease index and yield models were able to predict significant portions of the phenotypic variation between entries at most environments. These results suggest that it may be possible to estimate resistance to SDS and grain yield in soybeans using spectral reflectance in breeding populations.
Keywords: Soybean breeding; Disease resistanceSpectral reflectance